Freire and Gandhi :Their relevance for social work education - Lata Narayan (International Social Work 43(2): 193-204, 2004)
Paulo Freire and Mohandas Karamchand Gandhi were two stalwarts on the international scene who, through their own experiences and initiatives, made vital contributions in the field of education and influenced change processes in their countries. Their larger goals were similar to those of professional social work and, thus, social work education. This article attempts to study their initiatives in education in terms of the core values and the role of education in society and methodology, and to relate these to social work education. This is not an exhaustive coverage of their thoughts and ideas, and neither is it an in-depth critique of the concepts used by them. It is also accepted that internationally there are no uniform standards for training of social workers (Hokenstad and Kendall, 1997).